Respuesta :

Answer:

3

Step-by-step explanation:

Hello!

It is asking for the answer is p is equal to 3 so we put 3 in for p

3 = 2n - 3

Add 3 to both sides

6 = 2n

Divide both sides by 2

3 = n

The answer is 3

Hope this helps!

Answer:

n = 3

Step-by-step explanation:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation:

*3-(2*n-3)=0

Pull out like factors:

*6 - 2n  =   -2 • (n - 3)

Solve:

*-2   =  0 (This has no equation so we solve for the next side.)

*n-3 = 0 (Add 3 to both sides)

ACCESS MORE